Research and implementation of reconfigurable SM4 cryptographic algorithm based on HRCA - Xiao ZHANG; Qinglei ZHOU; Bin LI (网络与信息安全学报)
For the application scenarios that require high throughput and high security at the same time,based on HRCA,a high-performance scalable SM4 implementation scheme was proposed.Firstly,SM4 was formed to different calculation units of different granularity,and a general coarse-grained reconfigurable calculation unit was designed.Then,various mapping strategies were given for the purpose of satisfying different encryption modes,and the algorithm was mapped to the reconstructed computing unit according to different strategies.Finally,the SM4 overall architecture was optimized by dividing the control plane and the data plane.The experimental results show that using the proposed method,the SM4 algorithm has a significant improvement in throughput under lower resource consumption.